Perancangan Identitas Visual Kampanye Edukasi Pemanfaatan Alat Sanitasi Menstruasi Ramah Lingkungan - Salsabila Warda Wahota; Aileena Solicitor Costa Rica El Chidtian; Aditya Rahman Yani (Universitas Informatika dan Bisnis Indonesia, 2024)
Based on the results of a questionnaire, 98% of women aged 18-24 years still use conventional sanitary napkins. Meanwhile, conventional disposable sanitary napkins have a negative impact on the environment and women's health. Based on scientific articles, the sanitary napkin waste takes 500-800 years to decompose, which contributes to environmental problems. Conventional sanitary napkins are also made from chemicals such as chlorine, dioxins, and phthalates, which can cause various health problems, including cancer risk. One of the ways to raise awareness of these negative impacts is by conducting educational campaigns to use sustainable menstrual sanitary products. However, the campaign activities still do not have a visual identity. So, it is necessary to create a campaign visual identity to increase awareness and increase audience interest in campaign activities. The process of making this project was carried out by taking data through interviews, journals, questionnaires, books, and validated websites, then analyzed using descriptive qualitative methods. The result of this design is a logo that can display the visual identity of the campaign.